Корреляционно-спектральная модель контроля автокогерентности термодинамических процессов - Кропачек, Ольга Юрьевна (НТУ "ХПИ", 2017)
Усовершенствована математическая модель для расчёта коэффициента автокогерентности с целью выявления частотной и временной нестационарности переходных случайных тепловых процессов. Показана возможность использования коэффициента частотной нестационарности по сдвигу для контроля экстремальных значений многомерных тепловых процессов при существенных ограничениях интервала времени наблюдения. Доказана возможность экстраполяции контролируемых многомерных термодинамических параметров по усовершенствованным коэффициентам автокогерентности с использованием вероятностно обоснованной процедуры локального прогнозирования.

The mathematical model for computing the coefficient of auto-coherence has been improved to detect the frequency and time nonstationarity of transient random thermal processes. The possibility of using the factor of frequency nonstationarity in the shift to control the extreme values of multidimensional thermal processes is shown under significant limitations of the observation time interval. The possibility of extrapolation of the controlled multidimensional thermodynamic parameters by the improved coefficients of auto-coherence with the use of a probabilistically grounded procedure of local prediction is proved. Equations for predicting error variances for alternative computational procedures are obtained and conditions for improving forecasting efficiency are determined. The possibility of increasing the accuracy of the statistical control of thermal processes when extrapolating by the improved coefficients of auto-coherence is proved.
Correlation-spectral model for controlling auto-coherence of thermodynamic processes
Keywords: тепловые процессы; температура; прогнозирование; диагностика; идентификация; когерентность; thermal processes; temperature; prediction; diagnostics; identification; coherence